Argument-based human–AI collaboration for supporting behavior change to improve health - Kilic, Kaan; Weck, Saskia; Kampik, Timotheus; Lindgren, Helena (Frontiers in Artificial Intelligence, 2023)
This paper presents an empirical requirement elicitation study for an argumentation-based digital companion for supporting behavior change, whose ultimate goal is the promotion and facilitation of healthy behavior. The study was conducted with non-expert users as well as with health experts and was in part supported by the development of prototypes. It focuses on human-centric aspects, in particular user motivations, as well as on expectations and perceptions regarding the role and interaction behavior of a digital companion. Based on the results of the study, a framework for person-tailoring the agent’s roles and behaviors, and argumentation schemes are proposed. The results indicate that the extent to which a digital companion argumentatively challenges or supports a user’s attitudes and chosen behavior and how assertive and provocative the companion is may have a substantial and individualized effect on user acceptance as well as on the effects of interacting with the digital companion. More broadly, the results shed some initial light on the perception of users and domain experts of “soft”, meta-level aspects of argumentative dialogue, indicating potential for future research.